Lecture 12 Updated for 2005

Lecture 12 Updated for 2005

Notes for Quantum Mechanics Richard Seto Lecture 12 Updated for 2005 Date 2005,@D 11, 4, 17, 37, 42.5609024 8 < Lecture 12 Changing basis (or "representation") We have decided to use the Sz basis, i.e. + and - . Suppose we want to switch to the Sx basis. Is the a way to do this? Before we answer this, lets see if there is a way to go from one set of eigenkets say + and - , to another set, perhaps ` ` Sx+ and Sx- . Lets think of this more generally as A=Sz with eigenkets ai . Is there a way to find a different set of ` ` † \ † \ ` ` eigenkets of another operator B=Sx with eigenkets bi ? In general we can let A and B be any two operators which represent observables so that the kets a and b are complete, orthogonal eigenkets.† \ Let us† \suppose that we have an ` i i operator† \ U† which\ does this. † \ † \ ` † \ † \ i.e. bi =U ai . (1) ` The operator U will be a special kind of transformation matrix called a unitary operator. † \ † \ ` ` † ` ` ` ` † ` ` -1 ` † A unitary operator U is one in which U U=1 and UU =1 This also means U =U (2) ` ` Now we want an operator U such that bi =U ai . By construction this will be k bk ak (3) ` Proof: U ai = k bk ak ai = k bk dki= bi QED † \ † \ ⁄ † \ X » ` † ` ` we can also show that this is unitary: U U= j a j b j k bk ak = j k a j b j bk ak = j a j a j =1 ` Now we can† think\ ⁄ of† U\inX a matrix» \ ⁄notation.† \ The† matrix\ elements are (see lecture 7) ⁄ † \ X »⁄ † \ X » ⁄ ⁄ † \X † \ X » ⁄ † \X » ` ` a1 b1 a1 b2 ai U a j = ai k bk ak a j = ai b j so for the a two component case U= (4) a2 b1 a2 b2 i X † \X † \ y where we haveX used» † (3).\ NowX » ⁄lets† see\ Xhow» we\ canX »use\ this. j z k X † \X † \ { We have typically written things in the Sz basis, but suppose we want to switch to a different basis, say Sx . How do we do Essential Mathematica for Students of Science © James J. Kelly, 1998 2 qm12.nb this? First lets start out by figuring out how to change the basis of kets. In the Sz basis we write a = + + a + - - a . ` ` ` So that we can write this symbolically as a = a c = a a a where the a are eigenkets of A and A=S . We see ` i ` i i i i i i ` ` z that the coefficients ci = ai a . Now lets let B=Sx and bi are the eigenkets. In general we† can\ † let\X A† and\ † B\X be† any\ two operators which represent observables so that the kets ai and bi are complete, orthogonal eigenkets. Remember ` ` † \ ⁄ † \ ⁄ † \ X † \ † \ ai ai = 1 and i bi bi =1 Then we can write i X † \ † \ ' a = i ai ai a = ij b j b j ai ai a = j b j i b†j a\i ai †a \ So we can now write a = j b j c j where the new ' ` ‚coefficients† \ Y ° b j a =c j⁄= †i \bXj a†i ai a . Thinking of this in matrix notation is particularly nice since originally in the A a1 a basis we write a column vector † \ ⁄ † \ X † \ ⁄ † \ X † \aX2 a† \ ⁄ † \ ⁄ X † \ X † \ † \ ⁄ † \ X † \ ⁄ X † \ X † \ b a b a b a a a X † \ 1 1 1 1 2 1 We can transform toji the newzy basis as follows: = . (5) j z b2 a b2 a1 b2 a2 a2 a k X † \ { Notice how this matrix multiplication does exactly the samei Xthing† \ asy thei X sum.† \XNow notice† \ yi thatX †this\ y matrix is just the ` j z j zj z transpose-complex conjugate of U so we can write k X † \ { k X † \X † \ {k X † \ { b1 a ` † a1 a ` =U where it is now understood that U is in matrix notation. i.e. (6) b2 a a2 a ` † (7) (newi X †basis)=\ y Ui X(old† basis)\ y j z j z k X † \ { k X † \ { Example: Lets first recall from Lecture 8: 1 1 Sx; ≤ = ÅÅÅÅÅÅÅÅÅÅ ( + ± - ) Sy; ≤ = ÅÅÅÅÅÅÅÅÅÅ ( + ±i - ) (a) 2 2 1 1 + = ÅÅÅÅÅÅÅÅÅÅ ( Sx + + Sx - ) - = ÅÅÅÅÅÅÅÅÅÅ ( Sx + - Sx - ) (b) 2 è!!!! 2 è!!!! † \ 1 † \ † \ † \ 1 † \ † \ + = ÅÅÅÅÅÅÅÅÅÅ ( Sy + + Sy - ) - = ÅÅÅÅÅÅÅÅÅÅÅÅÅ ( Sy + - Sy - ) (c) è!!!!2 è!!!!2 i † \ † \ † \ † \ † \ † \ Now lets take ± as the old basis and Sx± as the the new basis è!!!! è!!!! † \ † \ † \ † \ † \ † \ 1) find the representation of ± in the Sx± basis. We know what the answer should be just by looking at (b). 1 1 1 1 1 1 It should be + = ÅÅÅÅÅÅÅÅÅņ \ ( Sx + + Sx - ) U ÅÅÅÅÅÅÅÅÅÅ and - =† ÅÅÅÅÅÅÅÅÅÅ\ ( Sx + - Sx - ) U ÅÅÅÅÅÅÅÅÅÅ in the Sx± basis. 2 2 1 2 2 -1 Its very important that we recall† \ we are in† the\ Sx± basis! Lets now use what we learned to see if we get the è!!!! è!!!! i y è!!!! è!!!! i y same answer.† \ † \ † \ j z † \ † \ † \ j z † \ ` old1 new1 old1 new2 + Sx +k {+ Sx - + + + - + k+ -{ - 11 UU = == ÅÅÅÅÅÅÅÅÅÅ1 = ÅÅÅÅÅÅÅÅÅÅ1 old2 new1 old2 new2 - Sx + † - S\x - 2 - + + - - + - - 2 1 -1 ` † 11 1 0 U = ÅÅÅÅÅÅÅÅÅÅ1 so using (7) we can write ± which in the original basis is just and i X 2 1† -1\X † \ y i X † \X† \ y è!!!! i X †H† \ † \L X 0†H† \ †1\L y è!!!! i y j z j z j z j z k X † \X † \ { k X † \X† \ { k X †H† \ † \L X †H† \ † \L { k { è!!!! i y i y i y j 11z 1 1 11† \ 0 1 j z j z + U ÅÅÅÅÅÅÅÅÅÅ1 k { = ÅÅÅÅÅÅÅÅÅÅ1 - U ÅÅÅÅÅÅÅÅÅÅ1 = ÅÅÅÅÅÅÅÅÅÅ1 in the new basisk as{ we kexpected.{ 2 1 -1 0 2 1 2 1 -1 1 2 -1 è!!!! i yi y è!!!! i y è!!!! i yi y è!!!! i y ` How does† \ this changej the zmatrixj z elementsj z †of\ operators?j Letszj findz out jfor anz operator X , Remembering that ` k {k { ` † k { k {k { k { bi =U ai and hence bi = ai U † \ † \ X » X » Essential Mathematica for Students of Science © James J. Kelly, 1998 qm12.nb 3 ` ` ` ` ` ` † ` ` bk X bl = bk 1 X 1 bl = bk ai ai X a j a j bl = ak U ai ai X a j a j U al = i j i j j ` † ` ` ` ` = ak U X U al or in somewhat symbolic notation where we mean that X ' is just the matrix for X in a new basis or Yrepresentation» » ] Y … … ] Y … ‚ † \ Y ° » ⁄ † \ X † \ ⁄ ⁄ X » » \ Y ° » ⁄ † \ X » † \ ` ` † ` ` XX'=U» XU † - \This is known as a similarity transformation in matrix algebra. ` † ` ` † ` ` So to summarize (ket in new basis)=U (ket old basis) AND X'=U X U (8) Example: ` 01 2) Now S in the ± basis is ÅÅÅÅÑ . Lets write it in the S ; ≤ basis. We again know what the answer has to x 2 10 x 10 be - it has to be ÅÅÅÅÑ . Lets use our methods and see if that is what we get. We use (8) 2 0 -1 ji zy † \ 11j 01z 11 11† \ 1 -1 20 10 ` † ` ` Ñ 1 1 k { Ñ 1 Ñ 1 Ñ U Sx U = ÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅ ÅÅÅÅ = ÅÅÅÅ ÅÅÅÅ = ÅÅÅÅ as we 2 2 i 2 1y -1 10 1 -1 2 2 1 -1 11 2 2 0 -2 2 0 -1 j z expected. k { è!!!! è!!!! i y i y i y i y i y i y i y j z j z j z j z j z j z j z TRACE k { k { k { k { k { k { k { Now we define a trace of an operator as the sum of the diagonal elements ` ` Tr(X )= ai X ai . This turns out to be INDEPENDENT of representation (9) i ‚ Y » » ] ` ` ` Proof: ai X ai = ai bk bk X bl bl ai = ai bk bk X bl bl ai = i i k l k l i ` ` ` ` ` = bl ai ai bk bk X bl = bl 1 bk bk X bl = dkl bk X bl = bk X bk QED k l i k l k l k ‚ Y » » ] ‚ Y … ‚ † \ Y ° » ⁄ † \ X † \ ‚ ‚ ‚ X » \ Y ° »† \X † \ A‚ few‚ other‚ thingsY † I \willX »ask\ youY °to prove» ] ‚ in the‚ problemY ° » set] Y ° » ] ‚ ‚ Y ° » ] ⁄ Y ° » ] ` ` ` ` Tr(X Y =Tr(Y X ) ` † ` ` ` Tr(U X U = Tr X ) Tr ai a j =dij (10) Tr bi Lai = ai bi L H H† \ X §L H† \ X §L X † \ Example: ` 01 10 3) Now in example 2 we had two representation of S as ÅÅÅÅÑ in the ususal ± and as ÅÅÅÅÑ in the x 2 10 2 0 -1 Sx; ≤ . The trace is the same (i.e. zero) in either basis. i y i y j z † \ j z k { k { Example:† \ Essential Mathematica for Students of Science © James J. Kelly, 1998 4 qm12.nb 4) now lets try something harder. Let's write Sx; ≤ in the Sy; ≤ basis. So we have ± old basis and Sy± new basis † \ † \ ` old1 new1 old1 new2 + Sy + + Sy - UU† \ = † \ == old2 new1 old2 new2 - Sy + - Sy - + + + i - + + - i - 11 ÅÅÅÅÅÅÅÅÅÅ1 = ÅÅÅÅÅÅÅÅÅÅ1 2 i X - +† + i \X- -† + -\ iy -i X † 2 \Xi -† i \ y j z j z ` † X 1† -i \X † \ X † \X† \ U =kÅÅÅÅÅÅÅÅÅÅ1 { k { è!!!! i X2 †H† 1\ i † \L X †H† \ † \L y è!!!! i y j z j z k X †H† \ † \L X †H† \ † \L1 { 1 k { 1 1 In the original ± basis Sx + U ÅÅÅÅÅÅÅÅÅÅ and Sx - U ÅÅÅÅÅÅÅÅÅÅ è!!!! i y 2 1 2 -1 j z k { 1 1 1 -i 1 1 1 - i 1 1 1 -i 1 1 1 + i In the new basis Sx + U ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅ - U ÅÅÅÅÅÅÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ = ÅÅÅÅ 2 2 è!!!!1 i iy 1 2 1 + i è!!!! i y2 2 1 i -1 2 1 - i † \ » \ j z » \ j z k { k { What does this mean? It means è!!!! è!!!! i yi y i y è!!!! è!!!! i yi y i y » \ j zj z j z † \ j zj z j z S + = ÅÅÅÅ1 (1-i) S + + ÅÅÅÅ1 (1+i) S - and S - = ÅÅÅÅ1 (1+i) S + + ÅÅÅÅ1 (1-i) S - x 2 y 2 y k {k { x k 2 { y 2 k y {k { k { Lets plug in for Sy ≤ and see if it makes sense 1 1 1 1 1 1 1 1 » Sx +\= ÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ (1-i)(» +\ + i - )+ ÅÅÅÅ» ÅÅÅÅÅÅÅÅÅÅ (1+i)(\ + -i -» )= ÅÅÅÅ \ÅÅÅÅÅÅÅÅÅÅ ( + + »i - -i +\ + - + » + - i\- +i + + - )= ÅÅÅÅ ÅÅÅÅÅÅÅÅÅÅ (2 + 2 2 2 2 2 2 2 2 +2 - ) » \ è!!!! è!!!! è!!!! è!!!! 1 = ÅÅÅÅÅÅÅÅÅÅ ( + + - ) So it checks out.

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    7 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us